Analysis Implementation Of Artificial Neural Network (ANN) In Character Recognition - Amalia S; Vandika A Y (Bandar Lampung University (UBL), 2017)
An artificial neural network is a representation of the 'artificial' of the human brain is always trying to simulate the learning process of the human brain. As nerves are the cells that process information in the brain and form a network as a whole. The term 'artificial' used in neural networks implemented using a computer program that is able to resolve a number of the calculation process during the learning process. An artificial neural network model a structure similar to the human brain. An artificial neural network has been used for image pattern recognition, character, and sound that is always trying to simulate the learning process of the human brain, one it is in the process of character recognition. How it works is an input image is converted to form a 10 x 10 matrix is then stored in a knowledge base file. The patterns saved earlier will be used as a pattern to be referenced at the time of the test pattern on the computer. The test is performed by comparing the test pattern with the pattern that has been stored on a computer by using ANN. Optical Character Recognition (OCR) is an application in pattern recognition to recognize the characters in digital images. OCR applications are already found in smartphones, especiallythe use of Android. Besides adequate hardware specifications for digital image processing, development of open-source library for image processing on the Android facilitate the development of software.